Globalizing Language Learning with Multicultural Sensitivity: How Ubiquitous Learning Technologies Support Cross-Cultural Language Acquisition - Ishak Bagea; Jack Davis; Emilie Bernard (International Journal of Language and Ubiquitous Learning, 2026)
Background. As the world becomes increasingly interconnected, language acquisition extends beyond merely mastering grammar and vocabulary to include understanding cultural nuances. Ubiquitous learning technologies have transformed the way languages are taught, making learning more flexible, accessible, and personalized. However, there remains a need for these technologies to address not only linguistic proficiency but also multicultural sensitivity, enabling learners to navigate cross-cultural communication effectively in a globalized world. Purpose. This study aims to explore how ubiquitous learning technologies can support language acquisition while fostering multicultural sensitivity. Specifically, it investigates the role of digital tools in bridging cultural gaps and enhancing learners’ ability to communicate across diverse cultural contexts. Method. A mixed-methods approach was employed, combining surveys, interviews, and usage data from learners who used mobile apps and online platforms for language learning. The study focused on how these technologies facilitated cross-cultural understanding, linguistic competence, and the development of intercultural communication skills. Results. The findings indicate that learners who used digital tools that incorporated cultural content and context-driven learning strategies showed significant improvements in both language proficiency and intercultural sensitivity. These learners demonstrated increased engagement and motivation, particularly in understanding cultural contexts and applying language in real-world scenarios. Conclusion. Ubiquitous learning technologies, when designed with multicultural sensitivity, play a critical role in supporting cross-cultural language acquisition. This research highlights the importance of integrating cultural awareness into language learning platforms to promote global communication skills.